Prognostic value of TAPSE in patients with septic cardiomyopathy: a retrospective observational cohort study - Liu, Haiyun; He, Huimin; Lin, Zhongbao; Lin, Xiankun; Jiang, Linqian; Huang, Long; Shang, Xiuling; Wang, Xincai (Frontiers in Medicine, 2025)
BackgroundSeptic cardiomyopathy is an acute myocardial injury caused by sepsis with high mortality. Tricuspid annular plane systolic excursion (TAPSE) is an important parameter for evaluating right ventricular systolic function, but its relationship with prognosis in septic cardiomyopathy has not been clearly elucidated.MethodsThis retrospective cohort study included 93 patients diagnosed with septic cardiomyopathy admitted to the intensive care unit (ICU). All patients underwent TAPSE measurements within 24 h of admission and were divided into abnormal (TAPSE < 1.6 cm, n = 33) and normal (TAPSE ≥ 1.6 cm, n = 60) groups. The primary outcome was 28-day all-cause mortality. Kaplan–Meier survival analysis was used to compare survival rates between the two groups, and Cox proportional hazards regression models were used to assess the independent association between TAPSE and 28-day mortality. Receiver operating characteristic (ROC) curve analysis was used to evaluate the predictive value of TAPSE for prognosis in septic cardiomyopathy.ResultsAmong the 93 patients, 25 (26.8%) died within 28 days after ICU admission. The mean TAPSE value in non-survivors was significantly lower than in survivors (1.24 ± 0.21 vs. 1.72 ± 0.20 cm, p < 0.001). Multivariate Cox regression analysis showed that, after adjusting for age, sex, lactate level, APACHE II score, left ventricular ejection fraction, and troponin I, TAPSE was independently associated with 28-day mortality. Dose–response relationship analysis indicated a negative linear relationship between TAPSE values and 28-day mortality, with each 0.1 cm decrease in TAPSE associated with a 40% increase in mortality risk (HR = 0.6, 95% CI: 0.48–0.74, p < 0.001). ROC curve analysis showed that TAPSE had an AUC of 0.881 (95% CI: 0.800–0.963) for predicting 28-day mortality, with the cut-off determined by Youden’s index of 1.55 cm, corresponding to a sensitivity of 80.0% and specificity of 80.9%.ConclusionTAPSE is independently associated with 28-day mortality in patients with septic cardiomyopathy and can serve as a valuable indicator for assessing short-term prognosis in these patients. Incorporating TAPSE assessment into routine examinations for septic cardiomyopathy patients may assist in identifying high-risk patients early for clinical monitoring.